Politocracy: An assessment of the coercive logic of the territorial state and ideas around a response to it - Translated by Johan Scott (Pretoria University Law Press (PULP), 2012)
Politocracy: An assessment of the coercive logic of the territorial state and ideas around a response to it by Koos Malan Translated by Johan Scott 2012 ISBN: 978-1-920538-10-1 Pages: xii 356 Print version: Available Electronic version: Free PDF available